Behavioral coping with chronic defeat stress in mice: A systematic review of current protocols - Alina Díez-Solinska; Zurine De Miguel; Garikoitz Azkona; Oscar Vegas (Neurobiology of Stress)
Social stress is the most significant source of chronic stress in humans and is commonly associated with health impairment. Individual differences in the behavioral coping responses to stress have been proposed to mediate the negative effects of stress on physical, behavioral and mental health. Animal models, particularly mice, offer valuable insights into the physiological and neurobiological correlates of behavioral coping strategies in response to chronic social stress. Here we aim to identify differences and similarities among stress protocols in mice, with particular attention to how neuroendocrine and/or behavioral responses vary according to different coping strategies, while highlighting the need for standardized approaches in future research. A systematic review was undertaken following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA statement). A total of 213 references were identified by electronic search, and after the screening, 18 articles were found to meet all the established criteria. We analyzed differences in the stress protocol, the characterization and classification of coping strategies and the physiological and behavioral differences according to coping. The results show that differences in behavioural expression under chronic social stress (coping) may also be associated with physiological differences and differential susceptibility to disease. However, this review also underlines the importance of a cautious interpretation of the results obtained. The lack of consistency in the nomenclature and procedures associated with the study of coping strategies for social stress, as well as the absence of a uniform classification, highlight the importance of using a common language when approaching the study of coping strategies. Thereby, this review encourages the development of a more defined method and criteria for assessing coping strategies, based on both behavioral and biological indicators.